2005
DOI: 10.1128/iai.73.7.3990-3998.2005
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mitogen-Activated Protein Kinases and NF-κB in the Regulation of Proinflammatory and Anti-Inflammatory Cytokines byPorphyromonas gingivalisHemagglutinin B

Abstract: Hemagglutinin B (HagB) is a nonfimbrial adhesin expressed on the surface of Porphyromonas gingivalis and has been implicated as a potential virulence factor involved in mediating the attachment of the bacteria to host cells. However, the molecular mechanisms underlying host responses to HagB and their roles in pathogenesis have yet to be elucidated. Mitogen-activated protein kinases (MAPKs) are activated following engagement of a variety of cell surface receptors via dual tyrosine and threonine phosphorylation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
64
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 39 publications
2
64
1
Order By: Relevance
“…33,34 p38 MAPK has been observed in airway epithelial cells and macrophages responding to environmental stresses, and this pathway appeared to be important for the secretion of pro-inflammatory cytokines and chemokines. [35][36][37][38] Our findings observed that CS stimulated the activity of p38 MAPK and the release of TNF-α and IL-1β in airway epithelial cells and in a mouse model. In our previous study, we showed that the p38 MAPK inhibitor SB203580 effectively reduced acrolein (a component of CS)-induced TNF-α release in BALF and the lungs of mice.…”
Section: Discussionmentioning
confidence: 65%
“…33,34 p38 MAPK has been observed in airway epithelial cells and macrophages responding to environmental stresses, and this pathway appeared to be important for the secretion of pro-inflammatory cytokines and chemokines. [35][36][37][38] Our findings observed that CS stimulated the activity of p38 MAPK and the release of TNF-α and IL-1β in airway epithelial cells and in a mouse model. In our previous study, we showed that the p38 MAPK inhibitor SB203580 effectively reduced acrolein (a component of CS)-induced TNF-α release in BALF and the lungs of mice.…”
Section: Discussionmentioning
confidence: 65%
“…Cell Extract Preparation-BMMs were stimulated with P. gingivalis and/or RANKL for different periods of time, and whole cell lysates from 10 6 cells were prepared as described previously (36,37). Briefly, cells were washed with PBS and then lysed on ice for 10 min in radioimmune precipitation assay lysis buffer (Upstate, Lake Placid, NY) freshly supplemented with 1 mM PMSF, 1 mM Na 3 VO 4 , 1 mM NaF, and 1 g/ml protease inhibitor cocktail (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, HNPs and HBDs are ideally positioned in the oral cavity to interact with an extensive and diverse group of both commensal and pathogenic microbial antigens. This includes adhesins of Porphyromonas gingivalis, a periodontal pathogen that induces proinflammatory cytokines (11,51,64).…”
mentioning
confidence: 99%